Peranan Badan Narkotika Kabupaten Kampar (BNK) Kampar Dalam Mencegah Peredaran Narkotika Di Kecamatan Tapung Kabupaten Kampar - Said Muhammad Faisal; Erdianto '; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
In the development of the current society, along with the increasing development of technology, transport, information and communication so that the impact on the patterns of people's lives. One of the negative effects inflicted as the abusive narcotics and illicit narcotics. It is necessary for the relevant agencies such as the Agency's Narcotics district (BNK) in order to prevent the occurrence of the circulation of narcotic drugs that are common in the environment of the community. The purpose of this thesis writing i.e. to know the role of Agency Narcotics district (BNK) Kampar in preventing the circulation of narcotics in district of Kampar Regency Tapung and to know the obstacles the Agency Narcotics district (BNK) Kampar in preventing the circulation of narcotic drugs in an effort to find out as well as Tapung Agency Narcotics district (BNK) Kampar overcoming obstacles in preventing the circulation of narcotics in district of Kampar Regency Tapung.This type of research can be classified in types of juridical sociological research, because in this study the authors direct research on the location or place that is examined in order to give a complete and clear picture of the problems examined. This research was conducted in district of Kampar Regency Tapung, while population and the sample is the entire parties relating to issues that are examined in this study, the data source used, the primary data and secondary data, techniques of collecting data in this study with interviews and research librarianship.From the results of research that the author do can be summed up, first the role of Agency Narcotics district (BNK) Kampar sub-district Tapung i.e. prevent the occurrence by carrying out socialization danger drugs and rehabilitate all users of narcotics by working with parents. The second obstacle the Agency Narcotics district (BNK) Kampar in preventing circulation in district Tapung i.e. lack of Agency budgets Narcotics district (BNK) Kampar, the lack of attention of parents towards children and the lack of cooperation between the society with the Agency Narcotics district (BNK) Kampar in terms of information occurrence of illicit narcotics in the subdistrict of Kampar Regency Tapung. The third attempt by the Narcotics district (BNK) Kampar overcoming obstacles in preventing the circulation of narcotics in district Tapung i.e. do prevention early to the rest of the community in the form of socializing and doing rehab to all users in the Subdistrict tapung and partners with the police in the form of Kampar Resort provides information in order to follow up the illicit happening in Tapung district of Kampar Regency.